LAYANAN BIMBINGAN KELOMPOK DENGAN PENDEKATAN POSITIVE BEHAVIOR SUPPORT DALAM MENINGKATKAN KEDISIPLINAN SISWA - Febri Dahlia; Aip Badrujaman; Happy Karlina Marjo (Jurnal Edukasi : Jurnal Bimbingan Konseling, 2018)
This research aims to determine the effect of applying group guidance with a positive behavior support approach to improve student discipline. The method used is true experimental design with a pretest-posttest control group design. The experimental group received group guidance for 9 sessions and in the control group did not receive training. The population in this research were class VIII students of SMP Negeri 229 Jakarta. The sampling technique used was simple random sampling, the sample in this study amounted to 20 people who had a low discipline category and were divided into two groups namely 10 experimental group students and 10 control group students. While the technique of analyzing data using descriptive statistics using empirical mean to see the average pretest and posttest scores in the experimental group and the control group. Can be seen from the comparison of the pretest score 274 and posttest 392 in the experimental group and get a score of 118 which means an increase of 69.8%. The results of testing the hypothesis with the Wilcoxson test, a signed ranking test indicates that the value of Asymp. Sig of 0.005 <0.05 (Significant) which means that through the results of the calculation can be interpreted as a significant difference between the experimental group and the control group and can prove what is meant by the guidance group that requires positive behavioral support to increase student discipline